Personality, Deliberate Practice, and Expertise Development in Sport - Alves Ballón Tedesqui, Rafael (Université d'Ottawa / University of Ottawa, 2019)
Conscientiousness-related personality traits are relevant predictors of many outcomes in achievement domains outside sport. They have also been associated with several outcomes in sport, however, their relative role on athletes’ deliberate practice (DP) and other criteria of expertise development has not been investigated. The overall aim of this dissertation was to examine the role of conscientiousness-related traits on sport expertise development. It had six specific purposes: (a) to examine the structural validity of conscientiousness-related measures; (b) to understand whether athletes’ DP amounts, skill level, and other criteria of expertise development could be predicted by these measures; (c) to identify the best personality predictor and combination of predictors that explained the maximal variance in different criteria of expertise development; (d) to examine whether grit facets predicted athletes’ practice engagement across a demanding sport season; (e) to explore coaches’ perspectives on the behavioural indicators of conscientious, gritty, and self-controlled athletes in training; and (f) to explore coaches’ views about how these personality traits may impact athletes’ quantity and quality of practice and development toward higher skill levels. The dissertation used a sequential explanatory mixed-methods design, wherein Phase 1 (Articles 1, 2, and 3) quantitatively pursued purposes (a) to (c), Phase 2 (Article 4) addressed (d), and Phase 3 (Article 5) qualitatively addressed (e) and (f). Article 1 tested the factor structure of the Brief Self-Control Scale in sport and showed distinct associations between self-control variables and (a) sport-specific practice amounts, (b) engagement in various practice contexts, and (c) threats to commitment to one’s sport, in a diverse sport sample. Article 2 conducted factor analyses of the Grit Scale in sport and examined a full latent variable model showing associations between grit variables and several criteria of expertise development. In particular, perseverance of effort associated with athletes’ weekly amounts of DP, engagement in different practice contexts, and skill level, while consistency of interests associated with athletes’ commitment to their sport. Article 3 comprised two studies. In Study 1, path analyses were used to assess the role of conscientiousness on criteria of expertise development. At the broad level, conscientiousness predicted athletes’ engagement in practice contexts and commitment to their sport; at the facet-level, achievement-striving was the best predictor of athletes’ weekly DP and engagement in practice contexts. The systematic test of the role of self-control (Article 1), grit (Article 2), and conscientiousness (Article 3, Study1) for key criteria of expertise development culminated with Study 2 of Article 3, which reported comparative analyses of the predictive ability of self-control, grit, and conscientiousness facets—which had shown to be significant predictors when assessed separately—for the criterion measures of sport expertise. Study 2 showed that (a) perseverance of effort was the best predictor of athletes’ weekly DP, engagement in mandatory practice, and the only predictor of higher skill level, (b) achievement-striving best predicted athletes’ engagement in optional practice, and (c) consistency of interests best predicted athletes’ commitment to their sport. Article 4 tested whether athletes’ self-reported levels of grit (broad and facets) were longitudinally associated with their coach-reported practice engagement throughout one sport season. Perseverance of effort was the grit variable most related to indicators of practice engagement, the only variable related to overall practice engagement across three time points, and the only variable marginally associated with athletes’ stability of practice engagement over time. Article 5 explored coaches’ views about the behavioural indicators of athletes’ conscientiousness, grit, and self-control in the daily training environment and how these traits impacted athletes’ training and development. Coaches described (a) conscientious athletes as systematic and detail-oriented, highly considerate of others, and highly engaged in self-regulation; (b) gritty athletes as those who persevere despite adversity and work hard in practice; and (c) self-controlled athletes as those who control impulses, resist temptations, and delay gratification. Coaches believe grit, conscientiousness, and self-control play important roles on athletes’ development toward higher skill levels, but results generally highlighted the preponderance of perseverance of effort. Potential mechanisms (e.g., conscientiousness—self-regulation—practice quality and conscientiousness—self-regulation—skill level) were highlighted to help explain the personality-expertise link found in Phases 1 and 2. This dissertation contributed to the literature on sport expertise by parsimoniously identifying conscientiousness-related personality traits that were associated with measures of athletes’ practice quantity, quality, and stability, commitment to sport, and higher skill level. Although several facets (i.e., perseverance of effort, consistency of interests, achievement-striving, self-discipline, and dutifulness) showed associations with practice and performance-related outcomes, this dissertation generally highlighted the role of grit facets. In particular, while perseverance of effort was the best predictor of athletes’ amounts of DP, the only grit variable associated with quality practice engagement over time, and the only predictor of higher skill level, consistency of interests was the best predictor of commitment variables. Furthermore, results based on coaches’ descriptions (a) provided behavioural indicators of conscientiousness-related traits that serve as reference points for practitioners aiming to help athletes develop desirable traits, (b) suggested that gritty athletes ‘work hard’ and conscientious athletes ‘work smart’, and (c) proposed mechanisms to explain the personality-expertise link found in the quantitative studies. Taken together, the results of this dissertation suggest that the tendency to persevere despite adversity and mindfully use self-regulated processes seems to be a powerful predisposition for athletes’ development toward expert levels of performance.
Keywords: personality; deliberate practice; expertise development; conscientiousness; grit; self-control